Mexico : Review Under the Flexible Credit Line Arrangement; Staff Report and Press Release on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
Mexico's strong policy framework has helped cushion the impact of the global crisis. The staff report highlights Mexico's review under the Flexible Credit Line Arrangement. The flexible exchange rate has adjusted, the inflation targeting framework has provided an anchor for expectations, and the fiscal rule and strengthened public sector balance sheets have averted disruptive moves in fiscal risk premia. Substantial liquidity has been provided to the foreign exchange market. Support has been put in place for a variety of domestic financial market segments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet